Face processing in young adults with autism and ADHD: An event related potentials study - Aydin, Ümit; Cañigueral, Roser; Tye, Charlotte; McLoughlin, Gráinne (Frontiers in Psychiatry, 2023)
Background: Atypicalities in perception and interpretation of faces and emotional facial expressions have been reported in both autism and attention-deficit/hyperactivity disorder (ADHD) during childhood and adulthood. Investigation of face processing during young adulthood (18 to 25 years), a transition period to full-fledged adulthood, could provide important information on the adult outcomes of autism and ADHD. Methods: In this study, we investigated event-related potentials (ERPs) related to visual face processing in autism, ADHD, and co occurring autism and ADHD in a large sample of young adults (N=566). The groups were based on the Diagnostic Interview for ADHD in Adults 2.0 (DIVA-2) and the Autism Diagnostic Observation Schedule-2 (ADOS-2). We analysed ERPs from two passive viewing tasks previously used in childhood investigations: 1) upright and inverted faces with direct or averted gaze; 2) faces expressing different emotions. Results: Across both tasks, we consistently found lower amplitude and longer latency of N170 in participants with autism compared to those without. Longer P1 latencies and smaller P3 amplitudes in response to emotional expressions and longer P3 latencies for upright faces were also characteristic to the autistic group. Those with ADHD had longer N170 latencies, specific to the face-gaze task. Individuals with both autism and ADHD showed additional alterations in gaze modulation and a lack of the face inversion effect indexed by a delayed N170. Conclusions: Alterations in N170 for autistic young adults is largely consistent with studies on autistic adults, and some studies in autistic children. These findings suggest that there are identifiable and measurable socio-functional atypicalities in young adults with autism.